Advanced Water Mathematics - Alvord, Michael; Blasberg, Regina; Open Textbook Library (Open Textbook Library, 2019)
Learning and Understanding Mathematical Concepts in the Areas of Water Distribution and Water Treatment
Section 1: Unit Dimensional Analysis -- Section 2: Geometric Shapes -- Section 3: Density and Specific Gravity -- Section 4: Chemical Dosage Analysis -- Section 5: Weir Overflow Rate -- Section 6: Water Treatment Math Detention Time -- Section 7: CT Calculations -- Section 8: Pressure, Head Loss, and Flow -- Section 9: Well Yield, Specific Capacity, and Drawdown -- Section 10: Horsepower and Efficiency -- Section 11: Per Capita Water Usage -- Section 12: Blending and Diluting -- Section 13: Scada and the Use of mA -- Section 14: Water Utility Management
In English.
Description based on online resource
Keywords: Earth Sciences -- Textbooks